Canadian Institutes of Health Research Support for Population Health Intervention Research in Canada - Di Ruggiero, Erica (Can J Public Health, 2009)
This paper outlines the results of an assessment respecting the extent of Canadian Institutes of Health Research (CIHR) funding in population health intervention research from 2001 to 2006. The analysis is presented within the context of the barriers and enablers to the generation, support for and uptake of population health intervention research. Given data quality concerns, the assessment should only be considered as an estimate of CIHR funding in this area. Eight percent of applications received in all CIHR competitions were in population health intervention research, of which 22% were funded over the period in question. The results show that the number and success of these applications tend to vary across peer review committees and among different types of funding competitions. To address identified gaps, the authors highlight several collaborative opportunities under way that are aimed at better support for population health intervention research in Canada.